PERANCANGAN ALAT MONITORING SUHU MENGGUNAKAN SENSOR MLX90614 PADAMESIN DIGITAL PRINTING XEROX WORKCENTRE BERBASIS IOT - Marhanif Choirunnisa Nurma; Dwi Hadidjaja Rosyid (LPPM Institut Pendidikan Nusantara Global, 2022)
Digital printing business is a business that is very interested in this era. Digital printing with a minimum size of A3+ has become a trend nowadays. There are many advantages that can be obtained from this A3 + digital printing machine. Printing needs that are chased by time are very suitable for using this machine. In this study the authors designed a thermometer for temperature on a digital printing machine using the MLX90614 sensor with the NodeMCU ESP8266 microcontroller, 16x2 LCD as display output, and a buzzer for warnings, in order to minimize striped printouts due to ink freezing due to overheating and other damage. The results of testing the design of this system are generated for the results of testing the temperature sensor readings obtained 100% accurate. This shows that the sensor is functioning properly from the results obtained with an accuracy rate of 100%. The results for reading the MLX90614 sensor with infrared thermometer readings are obtained by calculating the percentage error of 0.9%, which means the sensor is running well. The results of the test data show that the average delay of the overall data is 0.10 s.